TOMOGRAFIA COMPUTADA DE ALTA RESOLUCION EN NIÑOS CON DAÑO PULMONAR POR ADENOVIRUS: CARACTERIZACION Y CORRELACION CON FUNCION PULMONAR - Gloria Soto G; Marcela Linares P; Juan C. Díaz P; Juan A. Escaffi J; Fernando Pedersen M; Noldy Mardones C; D. Busel M; Samuel Gasc H; T.M. Pablo Arancibia N (Revista Chilena de Radiología, 2002)
Introduction: Respiratory tract infections caused by Adenovirus (ADV) can lead to long term lung sequelae. In our media it is the most frequent cause of chronic lung disease in children. High resolution computed tomography (HRCT) can characterize the anatomic alterations of this disease. Functional impairment is evaluated with spirometry, which only can be performed in collaborating patients. Purpose: Characterize the appearances of chronic lung disease secondary to ADV infection on HRCT, relate the extent of HRCT abnormalities to pulmonary function impairment, and determine if HRCT can be used to assess pulmonary function when functional tests cannot be performed. Material and methods: HRCT findings in 17 pediatric patients with post adenoviral chronic lung disease were analyzed. HRCT findings were correlated with spirometry in 11 of these children using the modified Bhalla score for bronchial dilatation and the modified Siegel score for mosaic lung attenuation. Results: HRCT findings were mosaic perfusion and bronchial wall thickening in 17/17, bronchial dilatation and centrilobular nodules in 16/17, atelectasis in 11/17, and tree in bud in 8/17. Very good correlation was found between the scores of mosaic lung attenuation and bronchial dilatation with the forced expiratory volume in one second. Conclusion: A characteristic pattern of findings on HRCT is present in children with post adenovirus chronic lung disease. There is good correlation between the severity of mosaic lung attenuation and bronchial dilatation with pulmonary functional impairment. These results suggest that HRCT findings can be used to assess pulmonary function in those children in which pulmonary function tests cannot be performed